PECULIARITIES OF FAMILY AND MARITAL RELATIONS OF THE KAZAKH AND KYRGYZ PEOPLE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article examines the peculiarities of Kazakh and Kyrgyz customs and traditions in family and marriage relations, as the most archaic and conservative elements of culturecan be observed here. Exogamous restrictions for marriage related to social, class, ethnic and tribalaffiliation of the groom and the bride, and their religion are considered.The ritual of matchmakingis described, including the customs according to which young children who had just been bornwere conscripted, a widow was given in marriage to the younger brother of her dead husband anda widower was married to the younger sister of his dead wife, the groom worked out a kalym in thehouse of his father-in-law, and the girls were abducted. The extracts concerning the matchmakingceremony from the Kazakh lyrical poem “Kozy-Korpesh and Bayan-Sulu” and the Kyrgyz epos“Manas” are given.The wedding ceremony is also described, where numerous ritual actions wereperformed that go back to both ancient social marriage institutions and religious-symbolic andmagical representations.
Keywords: family and marriage relations, Kazakhs, Kyrgyz, matchmaking, kalym, customs, traditions.